Isolation of wheat bran-colonizing and metabolizing species from the human fecal microbiota - De Paepe, Kim; Verspreet, Joran; Rezaei, Mohammad Naser; Hidalgo Martinez, Silvia; Meysman, Filip; Van de Walle, Davy; Dewettinck, Koen; Raes, Jeroen; Courtin, Christophe; Van de Wiele, Tom (PeerJ, 2019)
Undigestible, insoluble food particles, such as wheat bran, are important dietary constituents that serve as a fermentation substrate for the human gut microbiota. The first step in wheat bran fermentation involves the poorly studied solubilization of fibers from the complex insoluble wheat bran structure. Attachment of bacteria has been suggested to promote the efficient hydrolysis of insoluble substrates, but the mechanisms and drivers of this microbial attachment and colonization, as well as subsequent fermentation remain to be elucidated. We have previously shown that an individually dependent subset of gut bacteria is able to colonize the wheat bran residue. Here, we isolated these bran-attached microorganisms, which can then be used to gain mechanistic insights in future pure culture experiments. Four healthy fecal donors were screened to account for inter-individual differences in gut microbiota composition. A combination of a direct plating and enrichment method resulted in the isolation of a phylogenetically diverse set of species, belonging to the Bacteroidetes, Firmicutes, Proteobacteria and Actinobacteria phyla. A comparison with 16S rRNA gene sequences that were found enriched on wheat bran particles in previous studies, however, showed that the isolates do not yet cover the entire diversity of wheat-bran colonizing species, comprising among others a broad range of Prevotella, Bacteroides and Clostridium cluster XIVa species. We, therefore, suggest several modifications to the experiment set-up to further expand the array of isolated species.
Keywords: Human gut microbiota; Wheat bran-attached microbiota; Wheat bran-utilizing microbiota; Enrichment; Insoluble dietary particles